Prevalence of the GA risk haplotype of the rs1554483 and rs4864548 polymorphisms of the CLOCK gene associated with obesity and overweight in 26 populations - Flores, Sergio V.; Roco Videla, Ángel Gerardo.; Olguín Barraza, Mariela.; Maureira Carsalade, Nelson. (ARAN Ediciones, 2023)
Introduction: the GA haplotype of polymorphisms rs1554483 and rs4864548 has been associated with components of the metabolic syndrome such as high blood pressure and triglyceride levels; its carriers have a risk of obesity, 1.5 times higher than the rest of the population. Methodology: SNP rs1554483 and rs4864548 were obtained from 2504 individuals from the “1000genomes phase 3” database. Data were grouped into five macro populations (Africa, East Asia, South Asia, Europe and Latin America) covering a total of 26 populations. Differences in haplotype frequency between macro populations and populations were analyzed, for which Fisher’s F statistic was used. Results: the macro population of Africa presented the lowest frequency (17.9 %) and that of East Asia the highest (57.4 %). Within the populations there is a relative homogeneity in the frequencies, except in the case of those that make up the macro population of Latin America where the Peruvian population of Lima and the Puerto Rican population present much higher frequencies than the rest. Conclusions: the GA haplotype presents heterogeneity between macro populations, which suggests highly differentiated micro evolutionary pro-cesses between continents. We propose to study the association of the GA haplotype with other polymorphisms such as rs3749474, rs11932595 and rs6859524 that have also been associated with risk of obesity and factors associated with metabolic syndrome.
Prevalencia del haplotipo de riesgo GA de los polimorfismos rs1554483 y rs4864548 del gen CLOCK asociados a la obesidad y el sobrepeso en 26 poblaciones
Keywords: CLOCK gene; rs1554483; rs4864548; Síndrome metabólico; Obesidad